MANUSKRIP AL-QUR’AN DI KABUPATEN SINTANG (Sebuah Deskripsi Awal Atas Manuskrip Al-Qur`an Koleksi Istana Al-Mukarramah Kabupaten Sintang) - Rizki Putriani (IAT IAIN Pontianak, 2021)
Abstract The Qur'an manuscript collection from the Al-Mukarramah Palace, Sintang Regency, West Kalimantan has interesting characteristics, namely it has a fairly complete qiraat record. However, in this study, researchers only focused on descriptive studies as an initial effort to introduce the Qur'anic manuscripts collected by the Al-Mukarramah Palace to the public, especially in the academic world. This study uses a descriptive method, with the main source of the Qur'an manuscript collection of the Palace of Al-Mukarramah Sintang. The conclusion of this article is to describe – that the Manuscrip of the Al-Qur`an collected by the Al-Mukaaramah Sintang Palace was written by H. Abdul Karim and Sultan Nata in 1672, and the purpose of writing this Qur`an is to teach the basics of Islamic, especially the Qur'an to the zuriat of the kingdom and the children and grandchildren of the kings in the kingdom.